Islamic Dietary Menu Planning System For Breastfeeding Mothers - A. Nurdiana; M.A. Nurul Atiqa; H. Chek Zaini; I. Roesnita; A.M. Mohd Nazmi (IDOSI Publications, 2024)
Planning menus for individuals with different Personal Health Record (PHR) and individuals with special nutritional needs especially for pregnant and breastfeeding women are very challenging. The menus should guide the right amount of food intake for the mothers. This paper examines the user requirements for the development of an Islamic dietary menu planning system for breastfeeding mothers. The system provides guidelines on good nutrition and daily practices for lactating mothers. Most of the websites found in the Internet follow basic principles of menu planning but some are totally contrary to Islamic values. Therefore, this menu planning system not only provides on the calories intake and nutritional content in the food but also in line, according to the Islamic values. Key words: Breastfeeding Diet Islamic Menu Mother Planning System